2004
DOI: 10.1364/opex.12.002448
|View full text |Cite
|
Sign up to set email alerts
|

Sub-picosecond pulse generation employing an SOA-based nonlinear polarization switch in a ring cavity

Abstract: Abstract:We demonstrate the generation of sub-picosecond optical pulses using a semiconductor optical amplifier (SOA) and a linear polarizer placed in a ring-laser configuration. Nonlinear polarization rotation in the SOA serves as the passive mode-locking mechanism. The ring cavity generates pulses with duration below 800 fs (FWHM) at a repetition rate of 14 MHz. The time -bandwidth product is 0.48. Simulation results in good agreement with the experimental results are presented. ©2004 Optical Society of Ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
30
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 13 publications
(16 reference statements)
0
30
0
Order By: Relevance
“…The laser output is extracted from the cavity by a 10/90 fiber coupler, with which 90% power is fed back into the laser. The part surrounded by dashed lines is a general configuration of nonlinear polarization rotation in a SOA, which has been used for optical signal processing [12] and passive mode-locking [13]. The output is measured by an optical spectrum analyzer (ANDO AQ6317, resolution 0.01nm).…”
Section: Experiments Setup and Operation Principlementioning
confidence: 99%
See 1 more Smart Citation
“…The laser output is extracted from the cavity by a 10/90 fiber coupler, with which 90% power is fed back into the laser. The part surrounded by dashed lines is a general configuration of nonlinear polarization rotation in a SOA, which has been used for optical signal processing [12] and passive mode-locking [13]. The output is measured by an optical spectrum analyzer (ANDO AQ6317, resolution 0.01nm).…”
Section: Experiments Setup and Operation Principlementioning
confidence: 99%
“…So the SOA cannot support the multiwavelength geneneration with wavelength spacing as small as 0.08 nm. Note that the self-induced polarization rotation in the SOA has been utilized to mode-lock fiber laser and optical signal processing with nonlinear phase-shift created in the SOA and polarization discriminated in the polarizer [12,13]. In these cases, the output from the combination of a SOA and a polarizer increase with the incoming light intensity.…”
Section: Experiments Setup and Operation Principlementioning
confidence: 99%
“…Active modelocking using phase modulation in a SOA ring laser is implemented, while the details are described in [6]. The cavity also contains a nonlinear polarisation switch, which acts as an additional pulse compression element [7]. It will be shown that the ring laser outputs pulses with a duration of 1.5 ps (full width at half maximum, FWHM) at a repetition rate of 10 GHz.…”
mentioning
confidence: 99%
“…An essential building block in the cavity was a nonlinear polarisation switch that acted as a pulse compression element to compensate the dispersion in the fibre. Details concerning the nonlinear polarisation switch can be found in the context of passive modelocking in [7]. Shorter pulsewidth allows the flip-flop to be employed in higher OTDM bit-rate systems.…”
mentioning
confidence: 99%
“…The technological difficulties of making faster absorbers stimulated the search for ''artificial'' saturable absorbers which are characterized by ultrafast intensity-dependent losses, e.g., additive-pulse ML, nonlinear polarization rotation (NLPR), and Kerr lens mode locking (KLM) [4]. Among these methods, NLPR takes advantage of the lightwave polarization degree of freedom and it has recently been demonstrated in ML semiconductor lasers [5].…”
mentioning
confidence: 99%